Gaps in the implementation of national core elements for sustainable antimicrobial use in the WHO-African region - Fuller, Walter L.; Aboderin, Aaron O.; Yahaya, Ali; Adeyemo, Adeyemi T.; Gahimbare, Laetitia; Kapona, Otridah; Hamzat, Omotayo T.; Bassoum, Oumar (Frontiers in Antibiotics, 2022)
Antimicrobial resistance (AMR) has emerged as a leading global health and economic threat of the 21st century, with Africa bearing the greatest burden of mortality from drug-resistant infections. Optimization of use of antimicrobials is a core strategic element of the response to AMR addressing misuse and overuse as primary drivers. Effectively, this requires whole society comprising not only healthcare professionals, but also the public as well as government, engaged in a bottom-up and top-down fashion. We determined progress by Africa national governments in optimising antimicrobial drug use. September 2021-June 2022, all 47 WHO AFRO member states were invited to participate in the survey determining implementation of strategies to optimize antimicrobial use (AMU). We used the WHO antimicrobial stewardship (AMS) assessment tool: National Core Elements - A checklist to guide the country in identifying existing national core elements for the implementation of AMS Programs to obtain information from national AMR focal persons. The tool consists of four sections: national plans and strategies, regulations and guidelines, awareness, training and education as well as supporting technologies and data, with a total 33 checklist items, each graded 0-4. Responses were aggregated and analysed using Microsoft Excel 2020®. Thirty-one (66%) of 47 countries returned completed forms. Only eight (25.8%) countries have developed national AMS implementation policy incorporating defined goals, target and operational plans. There are no budget lines for AMS activities in 23 (74.2%) countries. The WHO AWaRe classification of optimising AMU has been integrated into the national essential medicines list or formulary in 19 (61.3%) countries. Incorporation of AMS principles and WHO AWaRe classification in to national clinical guidelines for management of infections are present in only 12 (38.7%) and 11 (34.5%) countries respectively. Though regulations on prescription-only sale/ dispensing of antibiotics exist in 68% of countries, enforcement is poor. Systems to identify pathogens and antibiotic susceptibility for optimal use of antibiotic are lacking in 38% of countries. In Africa, wide gaps exist for governments to implement core elements of optimising antimicrobial drug use. Responding to AMR is a long haul, technical and financial support need to be deployed to optimize use of antimicrobials.